Task security scheduling method for 5G+MEC based grid edge computing platform - Shimulin XIE; Ijie BA; Xiang ZHANG; Zeyi TANG; Weifan NIAN; Xujie LIU (Dianxin kexue)
In order to ensure the security of task scheduling of grid edge computing platform and the data quality required by task scheduling, a task security scheduling method of grid edge computing platform based on 5G + MEC was proposed.Combined with confidentiality service and integrity service, the security level model of task scheduling was constructed to restrict the risk in the process of scheduling and transmission of scheduling task queue, so as to realize the secure transmission of 5G core network.The priority queue type was confirmd, the minimum queue and the maximum queue was selected, the maximization of data resources and the task scheduling of MEC equipment was supported, and a distributed task scheduling model was built.Using Lyapunov candidate function to improve the stability of task scheduling, and the model was solved by alternating direction multiplier method to obtain the optimal solution of task security scheduling.The test results show that after the application of this method, the risk probability results fluctuate in the range of 0.15～0.35, and the fitting degree between the relevant data provided by MEC equipment and the scheduling task of core server is higher than 0.92, the quality score of task scheduling data is also higher than 0.94.